2018
DOI: 10.1534/g3.118.200360
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Arginine Methyltransferase PRMT-5 Regulates SER-2 Tyramine Receptor-Mediated Behaviors inCaenorhabditis elegans

Abstract: G protein-coupled receptors are 7-pass transmembrane receptors that couple to heterotrimeric G proteins to mediate cellular responses to a diverse array of stimuli. Understanding the mechanisms that regulate G protein-coupled receptors is crucial to manipulating their signaling for therapeutic benefit. One key regulatory mechanism that contributes to the functional diversity of many signaling proteins is post-translational modification. Whereas phosphorylation remains the best studied of such modifications, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…SPO-11 is the topoisomerase-like conserved protein that catalyzes meiotic DSBs so that the elevated levels of DSB formation observed in DBP exposed worms may be due in part to deregulation of spo-11 expression. prmt-5 encodes for the ortholog of human PRMT5, a protein arginine methyltransferase involved in the post-translational modification of a variety of proteins including histones and G protein-coupled receptors, thereby regulating transcription and signaling [91]. Interestingly, PRMT5 has been proposed to regulate the target gene specificity of p53 in mammals [74] and to negatively regulate apoptotic signaling in response to DNA damage in C .…”
Section: Discussionmentioning
confidence: 99%
“…SPO-11 is the topoisomerase-like conserved protein that catalyzes meiotic DSBs so that the elevated levels of DSB formation observed in DBP exposed worms may be due in part to deregulation of spo-11 expression. prmt-5 encodes for the ortholog of human PRMT5, a protein arginine methyltransferase involved in the post-translational modification of a variety of proteins including histones and G protein-coupled receptors, thereby regulating transcription and signaling [91]. Interestingly, PRMT5 has been proposed to regulate the target gene specificity of p53 in mammals [74] and to negatively regulate apoptotic signaling in response to DNA damage in C .…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pgen.1008529.g005 by a two-tailed unpaired t-test), an arginine methyltransferase involved in the modification of histones and receptors involved in signaling and transcription regulation, that could lead to altered gene expression or chromosome structure resulting in the observed increased levels of DSBs [56] (Fig 7).…”
Section: Dehp Exposure Leads To Germline-specific Change In the Exprementioning
confidence: 99%
“…Finally, the type III PRMT, including PRMT7, catalyzes the mono- and symmetrically di-methylated arginine residues. Recently, we and others demonstrated the physiological roles for PRMT1, PRMT5 and PRMT8 in the control of neural function and neurodegenerative diseases 14–16 . Lin et al and Bowitch et al showed critical roles of PRMT8 and PRMT5 in the neural development of zebrafish 15 and of SER-2 tyramine receptor-mediated behaviors in Caenorhabditis elegans 16 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others demonstrated the physiological roles for PRMT1, PRMT5 and PRMT8 in the control of neural function and neurodegenerative diseases 14–16 . Lin et al and Bowitch et al showed critical roles of PRMT8 and PRMT5 in the neural development of zebrafish 15 and of SER-2 tyramine receptor-mediated behaviors in Caenorhabditis elegans 16 , respectively. We have demonstrated that the PRMT1-mediated arginine methylation of the KCNQ channel contributes to the stabilization of neuronal excitability 14 .…”
Section: Introductionmentioning
confidence: 99%